Performance, physiological and immune responses of Nile tilapia Oreochromis niloticus fed extruded pellet diets with different binders - Eman Y. Mohammady; Ümit Acar; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Simon J. Davies; Ehab R. El-Haroun; Mohamed S. Hassaan (Aquaculture Reports, 2025)
The trial was conducted to investigate the effects of inclusion carboxymethyl cellulose (CMC) or calcium lignosulfonate (CLS) on the physical qualities of extruded Nile tilapia diet, growth performance, feed efficiency, physiological and immune response for 70-day. Three identical isonitrogenous and isoenergetic diet were formulated, 0 (control), 4 g CMC and 4 g CLS kg−1 diet and fed to tilapia with an average initial body weight (14.20 ± 1.22 g). Inclusion of CLS significantly improved the water stability, durability, bulk density, and sinking speed of the pellets compared to CMC and control diets (P ≤ 0.05). Compared to the control group, inclusion of 4 g kg−1 CLS recorded the highest weight gain (WG, 51.00 g fish−1), specific growth rate (SGR, 3.02 %, day fish−1) and aveage daily gain (ADG) (0.61 g fish−1). The highest activities of amylase (84.102.44 U L−1), lipase (958.3 ± 70.11 L) and trypsin (0.59 ± 0.18 ng ml−1) were detected in fish fed CLS group. The height and width of villi and goblet cell number in both the anterior and posterior intestines were significantly increased in fish fed CLS than other groups. The activities of alanine amino transferase (ALT) and aspertate aminotransferase (AST) levels substantially decreased in the CLS group compared to the control. While CLS supplementation significantly elevated serum total protein, globulin, and albumin levels compared with CMC group and control diet. No significant differences were found in serum lipid profile among fish fed experimental diets. Catalase and superoxide dismutase (SOD) were significanly higher in fish fed diet supplemented with 4 g CLS kg−1 compared with others group. Furthermore, immunoglobulin M (IgM) and complement factors (C3, C4), were significantly improved in fish fed diet contained CLS.